(untitled) (Zia e Tahqeeq, 2025)
Imam Ala al-Din Mughaltai was a renowned Hanafi scholar of Egypt who had a great impact on his subsequent Muslim thought. He was an Ash’ari theologian and produced numerous books in the field of Islamic Studies. His writings had always been in a wide circulation. His Al-Ilaam bil-Sunnah is comentry on Ibn-e-Majah’s Sunan. This commentary is known as Sharh Mughaltai. Imam Jalal al-Din Suyuti was another prominent Muslim Scholar of Egypt who had a great contribution in Islamic literature. He wrote numerous books in almost all fields of Islamic Studies i.e. Quranic sciences, Hadith and Fiqh, Theology and Sufism. Misbah al-Zujajah is one of his major books in Hadith. It is a commentary on Al-Sunan by Ibn Maja. This paper aims to compare both commentaries of Mughaltai and Suyuti. This study helps to understand the methodologies and styles of writing of both Egyptian scholars.